Accessing the southeastern Brazil 2014 drought severity on the vegetation health by satellite image - Campos Gomes, Ana Carolina [UNESP] (2017)
Droughts are natural events that can cause water scarcity and can consequently have undesired environmental, social and political effects. Because droughts are related to land use and land cover modifications, satellite images are used to monitor and identify drought episodes through indices as Standardized Precipitation Index based on rainfall data and vegetation-based indices as Normalized Difference Vegetation Index (NDVI). Changes in vegetation cover have as impact the increasing of the land surface temperature (LST) that is a significant indicative of drought occurrence. This work explored the NDVI-LST relation through the Vegetation Health Index (VHI) in a tropical environment in Tiet River, State of So Paulo, Brazil, in order to assess changes in vegetation condition in two periods (2000 and 2014). Results showed that stressed areas are coincident with areas presenting high rate of modification in land cover; this areas presented low values of VHI and high values of LST. The worst conditions are verified in 2014, the same period of the most severe drought occurrence that reduced storage capacity in reservoirs in Tiet River.